Estimating Productivity Loss Cost according to Severity of Vehicle Crash Injury - Rong-Chang Jou; Tzu-Ying Chen (Journal of Advanced Transportation)
This study estimates the productivity loss cost according to the severity of vehicle crash injury. A contingent valuation survey was conducted to estimate the willingness to pay (WTP) of vehicle crash offenders in Taiwan. In addition, a Double-Hurdle model was used to deal with the large number of zero WTP responses. The results show that the estimated productivity loss cost of vehicle crash ranges from 2,000 USD to 47,000 USD. In addition, as expected, the individuals’ WTP is positively related with education, average monthly income, share of vehicle crash responsibility, experience of moderate or worse vehicle crash injury, work days lost after a vehicle crash, and experience of receiving compensation for productivity loss from a vehicle crash. This study also demonstrates that the Double-Hurdle model was statistically superior to the Tobit model.